Case studies on digital transformation - Gleiß, Alexander,Pousttchi, Key,Gronau, Norbert,Bick, Markus (print, 2022)
Digital transformation (DT) has not only been a major challenge in recent years, it is also supposed to continue to enormously impact our society and economy in the forthcoming decade. On the one hand, digital technologies have emerged, diffusing and determining our private and professional lives. On the other hand, digital platforms have leveraged the potentials of digital technologies to provide new business models. These dynamics have a massive effect on individuals, companies, and entire ecosystems. Digital technologies and platforms have changed the way persons consume or interact with each other. Moreover, they offer companies new opportunities to conduct their business in terms of value creation (e.g., business processes), value proposition (e.g., business models), or customer interaction (e.g., communication channels), i.e., the three dimensions of DT. However, they also can become a threat for a company's competitiveness or even survival. Eventually, the emergence, diffusion, and employment of digital technologies and ...
Dissertation, Universität Potsdam, 2022
Keywords: Graue Literatur; Hochschulschrift; Aufsatzsammlung; Digitale Gesundheit; Digitale Plattformen; Digitale Transformation; Digitalisierung; Plattformökonomie; Digital Health; Digital Platforms; Digital Transformation; Digitalization; Platform Economy